Metformin Alleviates Fibrosis of Trabecular Meshwork Cells Induced by TGFβ2 Through the Activation of Autophagy - Jing Ren; Pengtao Wu; Mengli Liu; Xuan Zhang; Zilu Guo; Yihan Liu; Rumeng Zhao; Gang Wang; Shichao Duan; Haijun Li (Dose-Response)
Objective In this study, we investigated the protective effect of Metformin on fibrosis of trabecular meshwork cells induced by TGFβ2. Methods Transformed and primary human trabecular meshwork cells (HTMCs) were treated with TGFβ2 or Metformin alone or combination, western blotting and immunofluorescence staining assays to detect autophagy activity and fibrotic proteins expression levels. TGFβ2 or Metformin alone or combination were injected into the anterior chamber of mouse eye. Mouse intraocular pressure (IOP) was measured every week, mouse eye sections were conducted immunofluorescence staining to analyze Col1 and Col3 expression. pSmad3 level and localization to evaluate TGFβ/Smad3 pathway activity. Chloroquine phosphate was used to block autophagy-lysosome pathway. Results Metformin activates autophagy of HTMCs in a dose dependent manner and efficiently ameliorates TMCs fibrosis induced by TGFβ2 in vitro and in mouse model, and decreased elevated IOP caused by TGFβ2. Metformin promotes fibrotic proteins degradation through the autophagy-lysosome pathway. Conclusion Our study found Metformin could alleviates fibrosis of HTMCs induced by TGFβ2 and decreased elevated IOP in mouse model.